2002
DOI: 10.1002/yea.917
|View full text |Cite
|
Sign up to set email alerts
|

Helicase activity is only partially required for Schizosaccharomyces pombe Rqh1p function

Abstract: The RecQ-related family of DNA helicases is required for the maintenance of genomic stability in organisms ranging from bacteria to humans. In humans, mutation of three RecQ-related helicases, BLM, WRN and RecQL4, cause the cancer-prone and premature ageing diseases of Bloom syndrome, Werner's syndrome and Rothmund-Thompson syndrome, respectively. In the fission yeast Schizosaccharomyces pombe, disruption of the rqh1 + gene, which encodes the single Sz. pombe RecQ-related helicase, causes cells to display redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…We had shown that suppression of ⌬top3 lethality was suppressed more efficiently when rqh1 ϩ was deleted compared with when its helicase activity was inactivated (42). Ahmad et al (43) showed that recovery from S-phase arrest by Rqh1 only partially depended on its helicase activity. In S. cerevisiae, the ability of Sgs1 to suppress crossovers and reduce GC tract lengths is reportedly independent of its helicase activity (J. Nickloff, personal communications).…”
Section: The Suppression Of Scc By Rqh1 Is Independent Of Its Helicasmentioning
confidence: 99%
“…We had shown that suppression of ⌬top3 lethality was suppressed more efficiently when rqh1 ϩ was deleted compared with when its helicase activity was inactivated (42). Ahmad et al (43) showed that recovery from S-phase arrest by Rqh1 only partially depended on its helicase activity. In S. cerevisiae, the ability of Sgs1 to suppress crossovers and reduce GC tract lengths is reportedly independent of its helicase activity (J. Nickloff, personal communications).…”
Section: The Suppression Of Scc By Rqh1 Is Independent Of Its Helicasmentioning
confidence: 99%
“…Helicase-dead Rqh1 mutants have intermediate phenotypes for DNA damage sensitivity and suppression of top3⌬ lethality compared to the deletion mutant (2,39). We recently reported that while rqh1⌬ mutants show a decreased frequency of DSB repair by GC, a helicase-dead mutant (rqh1:K547I [39]) showed near-WT frequencies of GC (29).…”
Section: Resultsmentioning
confidence: 99%
“…Integration of rqh1 À DNA into the S. pombe genome Construction of strains rqh1-KA (ECS218) and rqh1-KR (ECS220) has been described previously (Ahmad et al 2002); however, strains ECS218 and ECS220 are themselves the result of backcrossing (the original strains correspond to ECS194 and 196, respectively). To integrate the rqh1 À truncation mutants into the S. pombe genome at the rqh1 + locus, the entire ORF, together with regions upstream and downstream of the rqh1 + gene, was excised from plasmids pECS208 and pECS213-220 using a combination of Sph I, Aat II and Sac I.…”
Section: Construction Of Rqh1 à Truncation Mutantsmentioning
confidence: 99%
“…The Escherichia coli RecQ protein (the prototype member of this family) and all other RecQ homologues tested possess ATP-dependent 3¢ to 5¢ DNA helicase activity (Umezu and Nakayama 1993;Karow et al 1997;Bennett et al 1998;Shen et al 1998;Ahmad et al 2002;Cui et al 2003). The Wrn protein also possesses an exonuclease domain at its N-terminal end (Shen et al 1998).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation